Keeping First Nations children at home: A few Federal policy changes could make a big difference - Wien, Fred; Blackstock, Cindy; Loxley, John; Trocmé, Nico (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
Jordan’s case illustrates one of several areas where the formulation of better federal child and family service funding policy for First Nations children and young people, could go a long way toward improving the lives of First Nation children on reserve.